Purification of Novel Lipase Lip4 Gene Cloned From Local Isolate of Bacillus Amyloliquefaciens in Escherichia Coli - Mustafa M. Omar (American Journal of Biology and Natural Sciences, 2025)
Lipase, an enzyme that catalyzes the hydrolysis of triacylglycerol, is of significant interest in the field of biotechnology. Especially in modern food industries, instead of traditional chemical reactions. In this study, different lipase-producing isolates were obtained from different sources by two-step screening and identified as Bacillaceae. The highest producer of these isolates was found to belong to Bacillus amyloliquefaciens and named MMO (OR701819.1) with an enzyme activity determined at 59.6 U/ml. The lip4 gene responsible for lipase in this strain was studied in detail, and it was found to involve 600 bp of nucleotides (OR744906.1), encoding for 199 amino acids. This gene was linked with the expression pET-28a(+) plasmid and cloned into high-efficiency Escherichia coli DH5α, used as a host. Lipase was found to be produced from recombinant bacteria with an enzyme activity higher than was expressed in a wild strain, demonstrating that post-translational modification was achieved. The lipase activity achieved was 199.3 U/ml, three times more than in the wild strain. The enzyme produced by the cloned cells was subjected to a purification process to homogeneity in three sequential phases. The results showed an increase in the enzyme activity, reaching 344.2 U/ml at the end of the final purification processes. The purification fold was found to be 11.2. The recovery rate of lipase during the purification process was determined to be 51.8%. Then it can be used in the medical field, such as drugs for the treatment of indigestion and stomach terrible, as well as in food technology.